2016
DOI: 10.1002/pc.24059
|View full text |Cite
|
Sign up to set email alerts
|

Removal of methyl tert‐butyl ether as a water pollutant by photodegradation over a new type of poly(methyl methacrylate)/TiO2 nanocomposite

Abstract: Methyl tert-butyl ether (MTBE), as a common oxygenate additive in gasoline, not only can enhance the octane number but also reduce exhaust emissions. Unfortunately, MTBE is a highly water soluble reagent and resistant to biodegradation. One of the most important methods for treatment of the MTBE contaminated is photodegradation over TiO 2 . In this research work, the immobilized TiO 2 nanoparticles in poly(methyl methacrylate) PMMA nanocomposite films, which prepared by ionic liquid-based microemulsion method,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Here, continuing previous research in microemulsion systems using the soft template method that proved to be very successful in fabricating varieties of nanomaterial, we report on the controllable synthesis of PMMA/Fe 2 O 3 hollow nanospheres composite. PMMA/Fe 2 O 3 hollow nanospheres composite was prepared based on the stepwise manner via a combination of W/O and O/W microemulsion.…”
Section: Introductionmentioning
confidence: 75%
“…Here, continuing previous research in microemulsion systems using the soft template method that proved to be very successful in fabricating varieties of nanomaterial, we report on the controllable synthesis of PMMA/Fe 2 O 3 hollow nanospheres composite. PMMA/Fe 2 O 3 hollow nanospheres composite was prepared based on the stepwise manner via a combination of W/O and O/W microemulsion.…”
Section: Introductionmentioning
confidence: 75%
“…Based on the potential application of the resulted nanocomposite in visible‐light active photocatalysis, they also emphasized that not only [bmim][BF 4 ] acts as a dispersing agent, but also using of [bmim][BF 4 ] sensitized TiO 2 nanoparticles as visible light active agent. [ 108–110 ]…”
Section: Il‐based Microemulsions To Prepare Polymer Nanocompositesmentioning
confidence: 99%
“…Based on the potential application of the resulted nanocomposite in visible-light active photocatalysis, they also emphasized that not only [bmim][BF 4 ] acts as a dispersing agent, but also using of [bmim][BF 4 ] sensitized TiO 2 nanoparticles as visible light active agent. [108][109][110] It is important to mention that introducing IL in a nanocomposite may establish improvement of its physical and mechanical properties. Recently Xu et al [111] showed that the presence of 1-ethyl-3-methylimidazolium tetrafluoroborate in PMMA nanocomposite for mediating dispersion of silica filler improves elevation of glass transition.…”
Section: Microemulsions Containing Hydrophilic Ilsmentioning
confidence: 99%
“…Photocatalysis found its way into basically all research fields during the last decade, and removal of MTBE is no exception. The photocatalytic decomposition of MTBE was studied using various semiconductor catalysts, which were modified or immobilized on the support, the catalysts were mostly based on TiO 2 [4][5][6][7][8] or ZnO [9][10][11].…”
Section: Introductionmentioning
confidence: 99%